ANALISIS KUALITATIF TERHADAP STRATEGI PEMBELAJARAN KOOPERATIF JIGSAW DALAM KONTEKS MATA PELAJARAN IPS - Tia Mahfudoh; Imas Mastoah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine in depth the effectiveness of implementing the Jigsawcooperative learning strategy in the Social Studies (IPS) learning process at theElementary School (SD) level. The approach used is a literature study, by collectingand analyzing various sources such as scientific journals, books, and articles thatare relevant to the implementation and impact of using the Jigsaw model ineducation. The findings in this study indicate that the Jigsaw method is able toencourage active student participation, strengthen collaborative interactions ingroups, and improve understanding of IPS materials. In addition, this strategycontributes to the development of social and communication skills betweenstudents. However, the success of implementing this strategy is greatly influencedby a number of factors, including teacher competence in managing the learningprocess, student readiness to collaborate, and the availability of sufficient facilitiesand time. Other challenges that arise include limited allocation of learning time inthe curriculum and disparities in abilities between group members. Overall, thisstudy concludes that the Jigsaw strategy has the potential to improve the quality ofIPS learning, as long as it is supported by adequate planning and facilities.